A review of qualitative methodologies used to explore patient perceptions of arts and healthcare. Issue 2 (14th August 2012) - Moss, Hilary; Donnellan, Claire; O'Neill, Desmond
Abstract : Although the importance of the arts in healthcare is increasingly recognised, further research is needed to investigate the mechanisms by which arts and health programmes achieve their impact. An overview of the qualitative methods used to explore patients' perceptions of these interventions is lacking. We reviewed the literature to gain insights into the qualitative methods used to explore patients' perceptions of the role of arts in healthcare with a view to identifying the most common methodologies used and to guide researchers embarking on research regarding patients' perceptions of arts in healthcare. Our results indicate a paucity of qualitative studies, a variety of methods used and variability of methodological rigour. Grounded theory and phenomenology were the most common approaches adopted, mixed methods approaches were relatively frequent, and versions of 'thematic' or 'content' analysis were commonly cited. Semi-structured interviews were the most popular data collection method. The emphasis of all of the studies was on active or participative arts engagement, with no focus on receptive engagement with the arts and aesthetics. It was concluded that careful consideration of appropriate methodology is important when researching such an exploratory and sensitive area. Individual interviews were most popular and might be appropriate when exploring personal, sensitive experiences. Mixed method studies possibly provide a comprehensive approach which might satisfy both the arts and healthcare settings need for evidence. It seems important to pay attention to rigour in any methodology chosen and a greater focus on receptive engagement with the arts might be encouraged in future research.